2003
DOI: 10.1186/1472-6785-3-9
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour of free-ranging walruses with notes on apparent dextrality of flipper use

Abstract: Background: Direct observations of underwater behaviour of free-living marine mammals are rare. This is particularly true for large and potentially dangerous species such as the walrus (Odobenus rosmarus). Walruses are highly specialised predators on benthic invertebratesespecially bivalves. The unique feeding niche of walruses has led to speculations as to their underwater foraging behaviour. Based on observations of walruses in captivity and signs of predation left on the sea floor by free-living walruses, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…At least one study has shown a slight right-hand advantage for rhesus monkeys but no bias in capuchins [23]. It is not restricted to primates; for example, some 77% of walruses display a preference for the right flipper when feeding [24]. Some creatures, though, are clearly left-handed-or left-"limbed."…”
Section: Handednessmentioning
confidence: 99%
“…At least one study has shown a slight right-hand advantage for rhesus monkeys but no bias in capuchins [23]. It is not restricted to primates; for example, some 77% of walruses display a preference for the right flipper when feeding [24]. Some creatures, though, are clearly left-handed-or left-"limbed."…”
Section: Handednessmentioning
confidence: 99%
“…At the same time, there is a growing body of evidence showing manual laterality in other mammalian groups. For instance, limb preferences at individual and/or group levels in various species-typical motor activities have been described in rodents (Mongolian gerbils [10], mice and rats [11-14]), carnivores (black bears [15], domestic cats [16-20], and dogs [21-24]), ungulates (horses [25-28], plains zebras and impalas [29], donkeys [30]), bats (Schreiber’s long-fingered bat [31]) and even in marine mammals such as pinnipeds (walruses [32]) and cetaceans (humpback whales [33], bottlenose dolphins [34], and Commerson’s dolphins [35]). Thus, some kind of phylogenetic continuity in the evolution of motor lateralization in mammals could be traced [36].…”
Section: Introductionmentioning
confidence: 99%
“…This may generalize to other species. For example, Levermann et al (2003) reported that some 77 per cent of walruses show a preference for the right flipper when feeding. The direction of the asymmetry may vary between species, though, since Sovrano (2007) reported a left-forelimb feeding bias in toads.…”
Section: Laterality In Non-human Species (A) Handednessmentioning
confidence: 99%